A High-Performance Split Ring Resonator Based Slotted Microstrip Patch Antenna for Fifth Generation Communications (Jagannath University Journal of Science, 2024)
This article presents a split ring resonator (SRR) based slotted microstrip patch antenna for 5G communications. SRR is used for increasing the resonating power and performance of the antenna. The core resonating frequency of the proposed antenna is 28 GHz. The Computer Simulation Software (CST) has been used for calculating, simulating, and optimizing the parameters and the dimension of the antenna. The structure of the antenna is very compact, having dimensions of (17 ×17× 1.6) mm3. Substrate used for building the antenna was made of FR-4 material which has a dielectric coefficient of 4.3 and a thickness of 1.6 mm. The proposed antenna is distinguished by its low return loss of -26 dBi, high gain of 5.95 dB, wide operating band of 4.05 GHz (percentage bandwidth of 14.46%), and high radiation efficiency of almost 62%.Jagannath University Journal of Science, Volume 10, Number II, Dec. 2023, pp. 94-107